1996
DOI: 10.1002/(sici)1097-4636(199609)32:1<45::aid-jbm6>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Surface chemical structure for soft contact lenses as a function of polymer processing

Abstract: The surface chemistry and topography of cast-molded Etafilcon-A and doubled-sided lathed Etafilcon-A soft contact lenses were determined to be significantly different. The variations in surface chemical and morphologic structure between the two lenses were the result of contact lens manufacturing methods. The surface of the cast-molded Etafilcon-A had a consistently less rough surface compared to the doubled sided lathed Etafilcon-A as determined by atomic force microscopy. The surface of the doubled sided lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 9 publications
1
17
0
Order By: Relevance
“…Polymacon lenses values of Rq ranging from 7 to 28 nm, Grobe et al [2] reported for Etafilcon-A lenses values of Rq ranging from 5.0 to 25.2 nm, and Maldonado et al [8] reported values of Rq ranging from 3.9 to 12.3 nm, which depend in all of these studies on the fabrication method and on the face of the lenses. These studies clearly show that the fabrication technique has a notable influence on the lens roughness, being the cast-molded lenses those showing lower Rq values.…”
Section: Topographic Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…Polymacon lenses values of Rq ranging from 7 to 28 nm, Grobe et al [2] reported for Etafilcon-A lenses values of Rq ranging from 5.0 to 25.2 nm, and Maldonado et al [8] reported values of Rq ranging from 3.9 to 12.3 nm, which depend in all of these studies on the fabrication method and on the face of the lenses. These studies clearly show that the fabrication technique has a notable influence on the lens roughness, being the cast-molded lenses those showing lower Rq values.…”
Section: Topographic Analysismentioning
confidence: 99%
“…The Atomic Force Microscopy (AFM) is a technique that becomes useful to determine these properties, as was pointed out in an earlier work by Rabke et al [1]. Consequently, several authors [2][3][4][5][6][7][8][9][10][11][12][13][14][15] performed studies on CLs and using the AFM technique, but none of them used the Peak Force Quantitative Nanomechanics mode to determine the nanomechanical properties, such as the adhesion or the Young modulus, also named elastic modulus.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The spin casting method generates contact lenses with the smoothest surfaces, followed by cast-molding and then lathe-cut lenses (Guryca et al, 2007;Grobe, 1996). All the lenses presented here were cast-molded, and their roughness parameters were similar to the ranges reported for other non surface-treated cast-molded lenses (Guryca et al, 2007).…”
Section: Contactmentioning
confidence: 99%